5*-6-42-12*12*-6=0
the answer is: 0
T(1) = 3, t(n) = -2t(n-1) + 1
So t(2) = -2(t(1)) + 1 = -2(3) + 1 = -5
t(3) = -2(t(2)) +1 = -2(-5) +1 = 11
t(4) = -2(t(3)) +1 = -2(11) +1 = -21
t(5) = -2(t(4)) +1 = -2(-21) +1 = 43
Answer:
➢ <em>The multiplication property of equality states that when we multiply both sides of an equation by the same number, the two sides remain equal. Example 1 : Lisa and Linda have got the same amount of money. ... Multiply both sides by 4.</em>
Step-by-step explanation:
<em>HOPE IT WILL HELP </em><em>YOU</em>
<em>
</em>
<em>#</em><em>c</em><em>a</em><em>r</em><em>r</em><em>y</em><em> </em><em>on </em><em>learning</em>
Answer:
40
Step-by-step explanation:
The range is the difference between the largest value and the smallest value in the data set.
minimum value = 21 and maximum value = 61
range = 61 - 21 = 40
Your answer is gonna be C.